Good teaching and its evaluation from standpoint of the disciplines at the University - M. I. Ramírez Garzón; Juny Montoya Vargas (Universitat Politècnica de València, 2018)
This  article  provides  a  qualitative exploration  on  stakeholder's  thoughts about good teaching and faculty evaluation in  different  disciplines.  Thus,  on  this studies result, future proposals for faculty evaluation could be considered. We used in-depth  interviews  for  collecting  data; its sources were eighteen professors and lecturers from thirteen fields of knowledge. Professors have an extensive experience: five  years  to  twenty  years  as  teachers or  lecturers.  In  addition,  some  of  the participants deal with the administrative duties at the University. The main results show  that  the  good  teaching  and  the faculty evaluation is associated with the professor ability for motivating students, to offer a stimulating learning environment, to connect students with their professions, to make disciples and to compliance with the  institutional  mission.  Likewise,  it  is emphasized that faculty members should be evaluated by their capacity for mastering in the areas they teach, the willingness of them to educational innovation, teacher professional development, and most of all by the learning they promote.